Working memory, processing speed and general intelligence: Possible models of relations with visuospatial working memory using the visuospatial computerized working memory battery (BIMeT-VE) - Injoque Ricle, Irene (2018)
Working memory is an active memory system serving the realization of complex cognitive tasks. Over the last decades’ research has centered on studying the relationship of this memory system or any of its components with different cognitive functions, such as intelligence. The aim of this study is to analyze the relation between visuospatial working memory, processing speed and general intelligence, and the possible mediation role of some of these variables. To carry out this work, two studies were conducted. On Study 1 participated212 Spanish speaking college students, and a Spanish visuospatial working memory battery was designed and validated -the visuospatial Computerized Working Memory Battery (Batería Informatizada de Memoria de Trabajo Viso-Espacial; BIMeT-VE)-. On Study 2 participated 114 Spanish speaking college students, and the relationship among visuospatial working memory, processing speed and general intelligence was analyzed. The results showed that general intelligence is directly supported by the processing speed and to maintain visuospatial information for short periods of time, and indirectly by the ability to concurrently process visuospatial information.